Fungsi dan Makna Simbolis Pohon Beringin dalam Kehidupan Masyarakat Bali - Ni Luh Sutjiati Beratha; I Made Rajeg; Ni Wayan Sukarini (Pusat Kajian Bali Universitas Udayana, 2018)
Balinese people seem to realize that their existence in this world has a high dependence on nature as a buffer of life. One of the natural elements, especially trees that are very functional in the life of Balinese people, is banyan (beringin). Beringin, which is referred to as the waringin, wandira, and grodha agung, is preserved in almost all customary villages in Bali. Recognizing the importance of banyan trees in Balinese life, this study aims to analyze two problems related to banyan trees from the perspective of their functions and meanings. Qualitative methods are applied and data is analyzed by discourse theory. The results show that banyan trees are used as a means of yadnya ceremonies in Bali and are useful for curing various diseases, both caused by naturalistic (sakala) and personalistic causes (niskala). Symbolically the use of banyan in a pitra yadnya ceremony in Bali is interpreted as a means of purification to improve the quality of the ancestral spirit in the process of unification with the gods.